Progress in bioengineering of myotropic adeno-associated viral gene therapy vectors - Liu, Jixin; Koay, Teng Wei; Maiakovska, Olena; Zayas López, Margarita Laura; Grimm, Dirk (Human gene therapy, 2023)
The ability to specifically, safely, and efficiently transfer therapeutic payloads to the striated musculature via a minimally invasive delivery route remains one of the most important but also most ambitious aims in human gene therapy. Over the past two decades, a flurry of groups have harnessed recombinant adeno-associated viruses (AAVs) for this purpose, carrying cargoes that were packaged either in one of the various wild-type capsids or in a synthetic protein shell derived by molecular bioengineering. In this study, we provide an overview over the most commonly used techniques for the enrichment of muscle-specific (myotropic) AAV capsids, typically starting off with the genetic diversification of one or more extant wild-type sequences, followed by the stratification of the ensuing capsid libraries in different muscle types in small or large animals. These techniques include the shuffling of multiple parental capsid genes, peptide display in exposed capsid loops, mutagenesis of individual capsid residues, creation of chimeras between two viral parents, or combinations thereof. Moreover, we highlight alternative experimental or bioinformatic strategies such as ancestral reconstruction or rational design, all of which have already been employed successfully to derive synthetic AAV capsids or vectors with unprecedented in vivo efficiency and/or specificity in the musculature. Most recently, these efforts have culminated in the isolation of unique clades of myotropic vectors called AAVMYO or MyoAAV that have in common the display of the amino acid motif RGD (arginine-glycine-aspartate) on the capsid surface and that exhibit the highest transduction rate in striated muscles of mice or nonhuman primates reported to date. Finally, we note essential looming improvements that will facilitate and accelerate clinical translation of these latest generations of myotropic AAVs, including the identification and utilization of capsid selection or validation schemes that promise optimal translation in humans, and continued efforts to enhance patient safety by minimizing hepatic off-targeting.